Bishop Konstanty Felicjan Szaniawski's failed foundation - Krzysztof Czyżewski (Folia Historica Cracoviensia, 2004)
The article presents bishop Konstanty Felicjan Szaniawski's failed attempts to fund the Wawel Cathedral.